The effect of overuse of smartphone on sleep quality in patients with multiple sclerosis (Annals of Medical Research, 2021)
Aim: The aim of this study was to investigate the relationship between sleep quality and smartphone use in patients with MS.Material and Methods: Expanded Disability Status Scale (EDSS) was administered to evaluate MS related disability in patients. Sleep quality was assessed by Pittsburgh Sleep Quality Index (PSQI). Smartphone addiction scale (SAS) was used to measure the frequency of smartphone use.Results: Fifty-six MS patients with a mean age of 36.35 ± 8.03 were included in the current study. All patients had relapsing remitting MS and EDSS scores were detected lower than 3. Sleep disorder was found in 22 patients (39.3%). No significant difference was found in MS patients with sleep disorder in terms of patient age and sex compared to MS patients without sleep disorder (p values respectively 0.687; 0.057). No significant difference was found in terms of duration of disease, medication and EDSS score (1.000; 0.256; 0.406). The mean SAS scores was found significantly higher in MS patients with sleep disorder (p=0.001). Conclusion: Overuse of smartphones in patients with MS may reduce sleep quality.Keywords: Multiple sclerosis; sleep quality; smartphone overuse.
Keywords: Multiple sclerosis; sleep quality; smartphone overuse.